Influences of different drying climates on Eucalyptus camaldulensis wood properties - Kılıç Ak, Ayşenur; Bektaş, İbrahim; Çiçekler, Mustafa; Tutuş, Ahmet (Maderas. Ciencia y Tecnología, 2021)
One of the most important disadvantages of the wood material, whose usage is becoming more and more widespread, is the dimensional instability that occur in its interaction with water. Therefore, studies to improve these drawbacks of wood, remains always up to date. For mentioned purpose in this study, some chemical, morphological, physical and mechanical properties of Eucalyptus camaldulensis woods, which were naturally dried in outdoor and indoor climate in Eastern Mediterranean (Kahramanmaraş province) atmosphere conditions of Turkey, were investigated. According to the results of the study, chemical properties of eucalyptus woods dried indoor were measured as merely 0,23 % higher than dried ones in outdoor. The results of morphological measurements indicated that the fiber dimensions of eucalypts wood dried in indoor were averagely 1,48 % lower than the ones dried out in outdoor. Also, as a result of statistical analysis, it was found that there were significant differences (ρ < 0,000) between the physical properties of eucalyptus wood samples in indoor and outdoor according to t-test. At the same time, as a result of t-test applied to determine effect of drying conditions on mechanical properties of eucalyptus wood, modulus of elasticity, compression, tensile, dynamic bending and shear strength did not cause any significant difference between indoor and outdoor, while bending and Janka hardness strengths showed significant differences at ρ < 0,000 level. Finally, when the data obtained as a whole is considered, it can be said that testing of eucalyptus wood which requires a very sensitive drying in different climates has important contributions on the subject. Regarding eucalypts, which has a high distribution area (20 million hectares) in the world, it is recommended to relevant institutions and organizations to expand and maintain such study in the future. Lastly, according to obtained data from this study, it can be said that the experiments of eucalyptus woods which requires a very delicate drying in different environments provide important contributions on the subject.